Advances in Intelligent Systems Selected papers from 2012 International Conference on Control Systems (ICCS 2012), March 1-2, Hong Kong - Lee, Gary (Advances in Intelligent and Soft Computing, 2012)
2012 International Conference on Environment Science and 2012 International Conference on Computer Science (ICES 2012/ICCS 2012) will be held in Australia, Melbourne, 15‐16 March, 2012.Volume 2 contains some topics in intelligent system. There are 51 papers were selected as the regular paper in this volume. It contains the latest developments and reflects the experience of many researchers working in different environments (universities, research centers or even industries), publishing new theories and solving new technological problems.   The purpose of volume 2 is interconnection of diverse scientific fields, the cultivation of every possible scientific collaboration, the exchange of views and the promotion of new research targets as well as the further dissemination, the diffusion of intelligent system, including but not limited to Intelligent System, Neural networks, Machine Learning, Multimedia System and Applications, Speech Processing, Image & video Signal Processing and Computer‐Aided Network Design the dispersion.   We are sure that the efforts of the authors as well as the reviewers to provide high level contributions will be appreciated by the relevant scientific community. We are convinced that presented volume will be a source of knowledge and inspiration for all academic members, researchers and practitioners working in a field of the topic covered by the book.